Gambaran Emotional Well-Being Pada Pasien Kanker Stadium Lanjut Di RSUD Arifin Achmad Provinsi Riau - Rahayu Annisa Fitri; Yulia Rizka; Ari Rahmat Aziz (Universitas Karya Husada Semarang, 2025)
Introduction: Advanced cancer patients often experience complex emotional challenges due to diagnosis, treatment, and lifestyle changes that must be faced. Emotional well-being is an critical perspective that ought to be considered since it can influence their generally quality of life. The reason of this think about was to decide the portrayal of enthusiastic well-being in progressed cancer patients. Method: This ponder could be a quantitative study with a descriptive inquire about plan employing a cross-sectional approach. The populace of this ponder were cancer patients with progressed cancer who were hospitalized in all cancer inpatient rooms at Arifin Achmad Healing center, Riau Area. The testing procedure utilized was purposive sampling, with 30 tests taken utilizing non-probability testing strategies by considering the incorporation criteria. The measuring instrument utilized was the FACT-G survey which has been approved and solid. The investigation utilized was univariate examination. Results : This study shows that the majority of respondents are 56-65 years old (53.3%), the majority are female (21 respondents) (70.0%). The majority of respondents are married (23 respondents) (76.7%), the majority with elementary school education (12 respondents) (40.0%), and the majority are housewives (16 respondents) (53.3%), the majority with income <Rp.1,500,000 (16 respondents) (53.3%). The majority of cancer types are breast cancer (12 respondents) (40.0%) with the majority of diagnoses >1 year (16 respondents) (53.3%). The results showed that 19 respondents (63.3%) had a high level of emotional well-being. Conclusion : Progressed cancer patients involvement a extend of complex feelings, such as fear, uneasiness, and misery, but too illustrate the capacity to acknowledge the circumstance and discover meaning within the circumstance at hand.